Answer:
g(-1) = -5
g(2a+1) = 16a+11
Step-by-step explanation:
Substitute the given value into the function and evaluate.
So for g(x) = 8x+3
You substitute g(-1)
So g(-1) = 8(-1)+3
That is how you get -5
Then g(2a+1)
So g(2a+1) = 8(2a+1)+3
Thats how you get 16a+11
Hope this helps. Mark as brainlist
The answer for this is 22.325
Answer:
The graph is positive and decreasing for all real values of x where x < -1
Step-by-step explanation:
we have
![f(x)=(x-3)(x+1)](https://tex.z-dn.net/?f=f%28x%29%3D%28x-3%29%28x%2B1%29)
The function is a vertical parabola open up
The roots (x-intercepts) are x=3 and x=-1
The vertex is the point (1,-4 ) is a minimum
using a graphing tool
see the attached figure
we know that
In the interval (-∞,-1) ---> the function is positive and decreasing
In the interval (-1,1) ---> the function is negative and decreasing
In the interval (1,3) ---> the function is negative and increasing
In the interval (3,∞) ---> the function is positive and increasing
therefore
The graph is positive and decreasing for all real values of x where x < -1
1-5/8=3/8
If he had 5/8 leftover, then he used 3/8.